PELUANG APARTEMEN FATMAWATI CITY CENTER SEBAGAI APARTEMEN BERKONSEP TOD - Putri, Sarina Ika; Suryadjaja, Regina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
Housing is a primary need after food and clothing. Rapid population growth leads to rising land prices, making landed houses increasingly difficult to access. Therefore, apartments as vertical housing are an alternative, especially in Transit Oriented Development (TOD) areas. TOD is a land use concept that emphasizes a mix of activity, mobility, connectivity, density, and high intensity and is pedestrian-friendly. TOD areas have a distance of 400-800 meters that can be reached within 5-10 minutes walk from the transit point. The concept has three types: city, sub-city, and neighborhood transit-oriented areas. Sub-city transit-oriented apartment types are preferred because of their more affordable prices. The Fatmawati area is an example of a strategic sub-city TOD, located in South Jakarta near TB Simatupang, and has Fatmawati City Center Apartment adjacent to the MRT station. The main purpose of this study is to determine the opportunities and threats of Fatmawati City Center Apartment located in TOD. This data is collected through surveys, observations, journals, magazine articles, and 98 questionnaires that have been distributed to Fatmawati MRT users. The results of this study indicate that the majority of respondents are interested in buying apartments in TOD because of the factors that are taken into consideration, namely the ease of accessing public transportation, workplaces, other destinations, and traffic congestion that tends to be smooth, but financial limitations are a factor in their consideration in buying apartments in TOD. The majority are interested in the 2-bedroom type with a size of 42-71 m2 and in the price range of 500-750 million. It is hoped that the results of this study can provide input to developers who want to develop apartments in TOD. Keywords: apartment; fatmawati; transit oriented development Abstrak Kebutuhan rumah adalah kebutuhan primer setelah pangan dan sandang. Pertumbuhan penduduk yang cepat menyebabkan kenaikan harga tanah, membuat rumah (landed houses) semakin sulit diakses. Oleh karena itu, apartemen sebagai hunian vertikal menjadi alternatif terutama di area Transit Oriented Development (TOD). TOD adalah konsep penggunaan lahan yang menekankan pada campuran aktivitas, mobilitas, konektivitas, kepadatan, dan intensitas tinggi serta ramah terhadap pejalan kaki. Area TOD memiliki jarak 400–800 meter yang bisa ditempuh dalam 5-10 menit berjalan kaki dari tempat transit. Konsep ini memiliki tiga tipe: kawasan berorientasi transit kota, sub-kota, dan lingkungan. Tipe apartemen yang berada di transit sub-kota menjadi pilihan karena harga apartemennya lebih terjangkau. Kawasan Fatmawati adalah contoh TOD sub-kota yang strategis, terletak di Jakarta Selatan dekat TB Simatupang, dan memiliki Apartemen Fatmawati City Center yang berdekatan dengan stasiun MRT. Tujuan utama dari penelitian ini adalah untuk mengetahui peluang dan ancaman dari Apartemen Fatmawati City Center yang berada di TOD. Data ini dikumpulkan melalui survei, observasi, jurnal, artikel majalah, dan 98 kuesioner yang telah disebarkan kepada pengguna MRT Fatmawati. Hasil dari penelitian ini menunjukkan bahwa mayoritas responden berminat membeli apartemen di TOD karena faktor yang menjadi pertimbangan yaitu kemudahan dalam mengakses transportasi umum,tempat kerja, tempat destinasi lain, dan kemacetan lalu lintas yang cenderung lancar, namun keterbatasan finansial menjadi faktor pertimbangan mereka dalam membeli apartemen di TOD. Mayoritas tertarik pada tipe 2 kamar tidur dengan ukuran 42-71m2 dan di kisaran harga 500-750 juta. Diharapkan hasil penelitian ini dapat memberi masukan kepada para pengembang yang hendak mengembangkan apartemen di TOD.